2021
DOI: 10.30892/gtg.35231-678
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Relationship Between Human Resources Management Practices in the Hospitality Sector and Service Innovation in Jordan: The Mediating Role of Human Capital

Abstract: This study is aimed to explore the relationship between Human Resources Management (HRM) and innovation in services and whether such a relationship is mediated by human capital. The data was gathered from the hospitality sector in Jordan. To evaluate the proposed hypotheses, Structural Equation Modeling (SEM) was used via partial modeling of least squares. The research findings provide clear evidence that the Service Innovation of Jordan's hospitality was positively influenced by HRM activities and human resou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 56 publications
(125 reference statements)
0
12
0
Order By: Relevance
“…Furthermore, this study addressed the effect of service innovation on travel intention in hypothesis 3 which indicated that service innovation is positively associated with the increase in travel intention. The better availability of services for the tourists travelling from various countries always require good services (Mahmoud, Al-Mkhadmeh, & Alananzeh, 2021;Tang et al, 2020) which has the potential to promote their travel intention to visit various parts of Thailand. Similar with the current study, literature reported the positive relationship between service innovation and tourist intention (Khuong & Giang, 2014;Yeh et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, this study addressed the effect of service innovation on travel intention in hypothesis 3 which indicated that service innovation is positively associated with the increase in travel intention. The better availability of services for the tourists travelling from various countries always require good services (Mahmoud, Al-Mkhadmeh, & Alananzeh, 2021;Tang et al, 2020) which has the potential to promote their travel intention to visit various parts of Thailand. Similar with the current study, literature reported the positive relationship between service innovation and tourist intention (Khuong & Giang, 2014;Yeh et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…The study is based on a working methodology represented by models and proposed technological systems that can be applied to the study area -the city of Aqaba in Jordan -with the aim of converting it into a smart tourist city, by relying on interactive technologies such as Wi-Fi, geographic information systems (GIS) and Remote Sensing (RS), Bluetooth technologies, GPS technologies, tablets (RFID), and reversible devices (NFC) (Oppermann, 2009;Huang et al, 2017;Dragović et al, 2018;Mahmoud et al, 2021). Based on the foregoing, the study relied on the use of the systemic approach based on analyzing the elements of the study focused on the inputs, processes, and outputs of smart applications in the management of tourist cities.…”
Section: Study Methodologymentioning
confidence: 99%
“…At the same time, the most common approach is that human resource management is "a strategic and logically consistent approach to managing the most valuable asset of an enterprise: employees who collectively and individually contribute to solving the tasks of the enterprise" (Armstrong, 2004). In the process, the materials of specialists analyzing the human resource management system in tourism and service at the international and regional levels have been studied, which show that HRM activities play a vital role in improving the efficiency of businesses, expanding their market share, personal initiatives and innovations in the service sector (Ardito and Messeni, 2017;Anderson et al, 2014;Mahmoud et al, 2021). A retrospective analysis, an analysis that represents the reflection of past trends, allowed us to identify the principal periods in the establishment and development of the human resource management system in the world, allowed drawing an analogy of this process within the framework of the formation of HRM in Kazakhstan, with the isolation of tourism as a separate direction in management activities that has special features.…”
Section: Methodsmentioning
confidence: 99%
“…While the production sector offers well-qualified employees, for example, graduates, with an exciting and dynamic career, international career opportunities, the tourism industry also needs a huge number of operational employees (Karamova, 2014). Qualified and trained human resources are a real asset of a company (Mahmoud et al, 2021). Now, three main stages of the reform of this process have been formed in the republic, suggesting a systematic transition from an exposition-mixed model to a career model based on the priority of the principle of meritocracy, efficiency and accountability to society.…”
Section: Introductionmentioning
confidence: 99%